Overnutrition Status Is Associated with Elevated Blood Pressure among Adolescents in Central Jakarta, Indonesia - Palimbong, Jason Emmanuel; Djaja, Prissilia Nanny; Vetinly, Vetinly; Tjhay, Francisca (Althea Medical Journal, 2025)
Background: Overweight and obesity are rising among Indonesian adolescents and are known risk factors for hypertension. This study aimed to examine the relationship between overnutrition status and blood pressure among adolescents.Method: A cross-sectional study was conducted from May to September 2024, among overweight and obese adolescents aged 12–16 years in Central Jakarta, Indonesia.  Nutritional status was determined by body mass index (BMI) Z-scores based on CDC growth charts, adjusted for sex and age. Blood pressure was measured using a digital sphygmomanometer and classified according to the 2017 AAP guidelines. Data were analyzed using chi-square tests. Results: A total of 98 adolescents participated (67.3% male; mean age 13 years). Overweight (49%) and obesity (51%) were almost equally distributed, with the highest BMI recorded at 46.7 kg/m². More than half (58.2%) had elevated blood pressure, with one case reaching grade 2 hypertension (143/84 mmHg). Overnutrition status was significantly associated with elevated blood pressure (p=0.044). Stratified analysis showed a strong association among males (p=0.005), where 42.4% of obese males exhibited elevated blood pressure, but no significant association was observed among females (p=0.58).Conclusion: Overnutrition is significantly associated with elevated blood pressure among adolescents, particularly in males. Early interventions promoting balanced nutrition, physical activity, and healthy lifestyle habits are critical to reducing the long-term cardiovascular risk in this age group.